Is Tom Right?: An Extended Review of N. T. Wright's Justification: God's Plan and Paul's Vision - Campbell, Douglas A. (Scottish journal of theology, 2012)
In this extended review I first describe Wright's complex account of the doctrine of justification in Paul, which combines emphases on the covenant, the lawcourt, Christ and eschatology and includes, further, important translation claims concerning ‘the righteousness of God’ as God's covenant faithfulness, ‘justification’ as vindication in a lawcourt setting, ‘works of law’ as sociological boundary markers, and ‘faith’ as speaking not infrequently of Christ's fidelity rather than the generic Christian's (although these last two things are not separate; the former grounds the latter making it a badge of Christian membership). I then suggest, second, that Wright needs to recognise more clearly a particular danger in the traditional approach to justification that he is trying to move beyond – ‘foundationalist individualism’, or ‘forward thinking’. That is, the traditional reading of justification in Paul understands him to be arguing and thinking forward, from a nasty, legalistic, and essentially Jewish, plight, to a solution which is a gospel generously grasped by faith alone. This narrative, rooted in a certain reading of Romans 1–4, creates a large number of difficulties. (It begins with natural theology. It characterises Judaism unfairly. It asks a lot of sinful individuals unenlightened by grace. And so on.) And I am not convinced that Wright's complex revisionist account of justification has avoided them all. In particular, (1) he continues to emphasise a particular notion of the lawcourt in Paul's argument and thereby unleashes an account of God's character primarily in terms of retributive justice and hence in terms of Western politics. (2) He tends to define the covenant before he has taken full account of christology. The covenant should be defined by christology, rather than the other way around. One sign that things have not been tied together here as they ought to be is the number of different definitions of Israel that Wright supplies – as many as four. Moreover (3) even his revisionist sociological account of ‘works of law’ reproduces a key difficulty in the older approach, i.e. a jaundiced description of Judaism. And (4) his account of faith in Abraham does not explicitly link Paul's controversial reification of Genesis 15:6 to a christological hermeneutic, as it needs to in order to avoid crass reductionism. But Wright's definitive account of Paul is not yet fully articulated, so suitable adjustments might well allay my concerns here, with various aspects of foundationalism presently appearing within his theological description.